Rh nanoparticles supported on graphene as efficient catalyst for hydrolytic dehydrogenation of amine boranes for chemical hydrogen storage. (12th January 2015) - Shen, Junfeng; Yang, Lan; Hu, Kai; Luo, Wei; Cheng, Gongzhen
Abstract Well dispersed 2.4 nm Rh nanoparticles (NPs) supported on graphene have been synthesized via a one-step in situ procedure by using methylamine borane (MeAB) as the reducing agent. Compared with other conventional supports, such as carbon black, SiO2, γ-Al2O3, and the physical mixture of Rh and graphene, the as-prepared Rh NPs supported on graphene exhibit superior catalytic activity towards the hydrolysis of ammonia borane. Kinetic studies of catalytic hydrolysis of amine boranes indicate that the as-synthesized Rh/graphene is first order with respect to Rh concentration. Among all the reported Rh-based catalysts, the Rh/graphene exhibits the highest turnover frequency (TOF) values of 325 and 146 min−1, the lowest activation energy (Ea) values of 19.7 and 16.4 kJ/mol, toward hydrolysis of ammonia borane (AB) and MeAB, respectively.